Stability of Human Immunodeficiency Virus Type 1 Proviral DNA in Whole-Blood Samples - Jennings, Cheryl (American Society for Microbiology (ASM), 2005)
The Roche Amplicor HIV-1 Test requires that whole blood be processed within four days of collection. However, this requirement may be too limiting for use in international settings. Thus, we demonstrate that blood may be processed up to 10 days after collection if maintained under ambient conditions (2 to 25°C).